Multicomponent syntheses of pyrazoles via (3 + 2)-cyclocondensation and (3 + 2)-cycloaddition key steps - Ignaz Betcke; Alissa C. Götzinger; Maryna M. Kornet; Thomas J. J. Müller (Beilstein Journal of Organic Chemistry, 2024)
Pyrazoles are rarely found in nature but are traditionally used in the agrochemical and pharmaceutical industries, while other areas of use are also actively developing. However, they have also found numerous other applications. The search for new and efficient syntheses of these heterocycles is therefore highly relevant. The modular concept of multicomponent reactions (MCR) has paved a broad alley to heteroaromatics. The advantages over traditional methods are the broader scope and increased efficiency of these reactions. In particular, traditional multistep syntheses of pyrazoles have considerably been extended by MCR. Progress has been made in the cyclocondensation of 1,3-dielectrophiles that are generated in situ. Limitations in the regioselectivity of cyclocondensation with 1,3-dicarbonyls were overcome by the addition–cyclocondensation of α,β-unsaturated ketones. Embedding 1,3-dipolar cycloadditions into a one-pot process has additionally been developed for concise syntheses of pyrazoles. The MCR strategy also allows for concatenating classical condensation-based methodology with modern cross-coupling and radical chemistry, as well as providing versatile synthetic approaches to pyrazoles. This overview summarizes the most important MCR syntheses of pyrazoles based on ring-forming sequences in a flashlight fashion.